Perempuan yang Menikah Dini: Peran Dukungan Sosial pada Subjective Well-Being - Baiq Windarti; Rina Rifayanti (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2026)
The phenomenon of early marriage still occurs in society despite the existence of marital laws setting the minimum marrying age at 19. In East Kalimantan, for example, 219 women were married early. This study was conducted to investigate the correlation between social support and subjective well-being among women who entered into early marriages, using a purposive sampling method. The object of this research were 100 women who got married before 19 years old, have been married for under five years, and live in East Kalimantan. The data collection methods used were subjective well-being and social support scales. Data analysis was performed using Pearson’s product-moment correlation. The research results indicate a correlation among social support and and subjective well-being in women who married early. The two variables had a positive corellation and the strength of the corellation was in the very strong category. The findings of this study are expected to serve as recommendations for the development of counselling or support programmes for women who married early, as well as efforts to prevent early marriage.